Малый бизнес в экономике Крыма: тенденции развития - Хаирова, Э. А. (Культура народов Причерноморья, 2014)
Статья посвящена исследованию сущности развития малого бизнеса в современных рыночных условиях. Анaлизу урoвня рaзвития мaлoгo бизнeсa в Крыму и в мирe в цeлoм. Выявлению проблем и тенденций развития малого бизнеса в Крыму. Обоснованию перспективных направлений эффективного функционирования малого бизнеса в Крыму. Стаття присвячена дослідженню сутності розвитку малого бізнесу в сучасних ринкових умовах. Аналізу рівня розвитку малого бізнесу в Криму та в світі в цілому. Виявлення проблем і тенденцій розвитку малого бізнесу в Криму. Обґрунтування перспективних напрямків ефективного функціонування малого бізнесу в Криму. The article explores the essence of development of small business in the modern market conditions. The study of the various interpretations of the category of "small business" in the modern economic literature. Assessment of development of small and medium businesses in the developed world. Dynamics of development of small and medium business in the Crimea. The value of small innovative business development in modern conditions. Recommendations on priority measures for the effective support and identify major prospects of development of small entrepreneurship at regional and local levels. Proposals to encourage small businesses to develop innovative activities.